The Strategic Role of Generation Z as Digital Human Resources in Increasing the Economic Value of Natural Resource Products in the Digital Era - Akhmad Aiyon Saifulloh; Hendro Siswanto; Ahmad Syaiful Bahri; Nurus Sobakh (International Journal of Technology and Education Research, 2026)
Indonesia is a country rich in natural resources and holds significant potential to support economic development. However, the utilization of these resources is often limited to the sale of raw materials, resulting in relatively low economic value. In the digital era, Generation Z has emerged as a human resource (HR) with high technological capabilities, creativity, and innovation, capable of increasing the economic value of natural resource-based products. This study aims to analyze the strategic role of Generation Z as digital HR in increasing the economic value of natural resource-based products in the digital era. The research method used was a literature review with a qualitative descriptive approach. Data were obtained from various sources such as scientific journals, books, government reports, and relevant publications. The results indicate that Generation Z plays a significant role in increasing the economic value of natural resource-based products through the use of digital technology, digital marketing, product innovation, e-commerce, and the development of digital entrepreneurship. With their digital capabilities, Generation Z can expand markets, increase the competitiveness of local products, and create higher added value for natural resource-based products. Therefore, improving the digital literacy and entrepreneurial skills of Generation Z is a crucial factor in supporting sustainable natural resource-based economic development.